Composite film based on two-dimensional black phosphorus material and preparation method and application thereof
By combining two-dimensional black phosphorus, carbon nanotubes and polyvinylidene fluoride to form a crosslinked structure, the problem of oxidation and conductivity instability of black phosphorus materials in the air is solved, and a high-performance flexible sensor material is achieved.
Patent Information
- Application Number
- CN202411337008.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Black phosphorus materials are prone to oxidation in the air, resulting in reduced performance and unstable conductivity, which limits their application in the field of flexible electronic devices.
Using a composite film of two-dimensional black phosphorus, carbon nanotubes and polyvinylidene fluoride, the crosslinking of carbon nanotubes and black phosphorus and the coating of polyvinylidene fluoride is formed to form a stable conductive network to improve conductivity and chemistry. stability.
It significantly improves the conductivity, mechanical strength and stability of the composite film, prevents oxidation, and is suitable for high-performance flexible sensor applications.
Smart Images

Figure CN119161679A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of black phosphorus nanomaterials, and in particular relates to a composite film based on two-dimensional black phosphorus material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the Internet of Things (IoT), wearable devices and flexible electronic technologies, the demand for high-performance, flexible, and ultra-thin sensors has increased significantly. Traditional sensor materials, such as silicon-based materials, have excellent performance, but their rigidity and brittleness limit their application in the field of flexible electronics. To meet this demand, new two-dimensional materials (2D materials) such as graphene and molybdenum disulfide (MoS2) have attracted much attention due to their excellent electrical, mechanical and thermal properties. However, although these materials have improved the performance and flexibility of sensors to a certain extent, there are still some limitations, such as complex preparation, high cost, and chemical instability in some cases.
[0003] Black phosphorus (BP), as an emerging two-dimensional material, has become a hot topic in the research of highly flexible sensor materials due to its unique physical and chemical properties. Black phosphorus has a direct band gap, excellent electrical properties, and anisotropic mechanical properties, which makes it show great potential in the fields of optoelectronics, electronics, and sensors. In addition, the high flexibility and mechanical strength of black phosphorus make it an ideal candidate material for manufacturing ultra-thin, bendable sensors.
[0004] Specifically, the two-dimensional structure of black phosphorus material can realize the preparation of sensors with nanometer thickness, which not only greatly reduces the volume and weight of the sensor, but also significantly improves the sensitivity and response speed of the sensor. In addition, black phosphorus material can be well combined with flexible substrate materials (such as PVDF, PDMS, etc.), so as to produce flexible sensors that can be attached to various complex surfaces and withstand multiple bending and stretching.
[0005] However, despite the great potential of black phosphorus in the field of flexible electronic devices, current research and application still face some challenges. For example, black phosphorus materials are easily oxidized in the air, resulting in a decrease in their performance; at the same time, they are unstable when conducting electricity. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a composite film based on two-dimensional black phosphorus material and a preparation method and application thereof. The composite film provided by the present invention is not easily oxidized in the air and has strong conductive stability.
[0007] In order to achieve the above object, the present invention provides the following scheme:
[0008] The present invention provides a composite film based on a two-dimensional black phosphorus material, comprising two-dimensional layered black phosphorus, carbon nanotubes and polyvinylidene fluoride, wherein the two-dimensional layered black phosphorus and the carbon nanotubes are cross-linked with each other, and the polyvinylidene fluoride is coated on the surfaces of the two-dimensional layered black phosphorus and the carbon nanotubes.
[0009] Preferably, the mass ratio of the two-dimensional layered black phosphorus to the carbon nanotubes is (3-4):1.
[0010] Preferably, the mass ratio of the two-dimensional layered black phosphorus to polyvinylidene fluoride is (3-4):1.
[0011] The present invention provides the composite film described in the above scheme, wherein the thickness of the composite film is 5 to 200 μm.
[0012] The present invention provides a method for preparing a composite film based on a two-dimensional black phosphorus material as described in the above scheme, comprising the following steps:
[0013] mixing black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent to obtain a mixed solution;
[0014] The mixed solution is printed onto a substrate, cured, and peeled off to obtain the composite film based on the two-dimensional black phosphorus material.
[0015] Preferably, the mixing of black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent comprises the following steps:
[0016] Under the protection of inert gas, black phosphorus, carbon nanotubes and a first polar organic solvent are mixed and ball-milled to obtain a black phosphorus-carbon nanotube mixed solution;
[0017] The polyvinylidene fluoride and the second polar organic solvent are first mixed to obtain a polyvinylidene fluoride solution;
[0018] The black phosphorus-carbon nanotube mixed solution and the polyvinylidene fluoride solution are mixed for the second time.
[0019] Preferably, the rotation speed of the mixing ball mill is 300-400 rpm, and the time is 12-24 hours.
[0020] Preferably, the second mixing is performed under ultrasonic conditions; the power of the ultrasound is 200-300W, and the time is 1-3h.
[0021] Preferably, the curing temperature is 100-120° C. and the curing time is 12-24 hours.
[0022] The present invention provides the use of the composite film based on the two-dimensional black phosphorus material described in the above scheme or the composite film based on the two-dimensional black phosphorus material prepared by the preparation method described in the above scheme in a sensor.
[0023] The present invention provides a composite film based on a two-dimensional black phosphorus material, including two-dimensional layered black phosphorus, carbon nanotubes and polyvinylidene fluoride, wherein the two-dimensional layered black phosphorus and the carbon nanotubes are cross-linked with each other, and the polyvinylidene fluoride is coated on the surface of the two-dimensional layered black phosphorus and the carbon nanotubes. In the present invention, carbon nanotubes (CNTs) are a commonly used nanomaterial for enhancing electrical conductivity. The combination of carbon nanotubes and black phosphorus can increase the conductive path between the two-dimensional black phosphorus and improve the conductive stability. Polyvinylidene fluoride is a typical flexible material. Combining polyvinylidene fluoride with black phosphorus can improve the stability of black phosphorus, solve the problem of easy oxidation, and provide conditions for flexible films.
[0024] The present invention adopts black phosphorus, carbon nanotubes and polyvinylidene fluoride composite, which greatly improves the conductivity, mechanical strength and stability of the film, filling the gap in the multifunctionality of existing materials.
[0025] The present invention provides a method for preparing the composite film described in the above scheme. The present invention evenly disperses highly conductive carbon nanotubes in a black phosphorus matrix and uses the excellent mechanical flexibility and hydrophobicity of polyvinylidene fluoride to coat the entire composite film, thereby not only forming an effective physical barrier to block the intrusion of oxygen and moisture, but also establishing a stable conductive network, greatly improving the conductivity and chemical stability of the black phosphorus material.
[0026] Furthermore, the present invention prepares a black phosphorus-carbon nanotube mixed solution (BP-CNT mixed solution) by ball milling, which can ensure that the black phosphorus material and the carbon nanotubes are mixed evenly and can reduce the possibility of black phosphorus oxidation during the mixing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 This is a scanning electron microscope image of the BP / CNT@PVDF film of Example 1;
[0029] Figure 2 Another scanning electron microscope image of the BP / CNT@PVDF film of Example 1;
[0030] Figure 3 is a scanning electron microscope thickness image of the BP / CNT@PVDF film of Example 1;
[0031] Figure 4This is a physical picture of the BP / CNT@PVDF film of Example 1;
[0032] Figure 5 This is a comparison diagram of X-ray photoelectron spectra of the BP / CNT@PVDF film of Example 1 and pure black phosphorus;
[0033] Figure 6 is the X-ray diffraction pattern of the BP / CNT@PVDF film of Example 1;
[0034] Figure 7 The Raman spectra of the BP / CNT@PVDF film and PVDF, BP and CNT of Example 1;
[0035] Figure 8 The IV curve of the BP / CNT@PVDF film of Example 1 under different pressures;
[0036] Fig. 9 The IT curve of the BP / CNT@PVDF film of Example 1 under different pressures;
[0037] Fig.10 This is the IP curve of the BP / CNT@PVDF film of Example 1 under gradually increasing pressure;
[0038] Fig.11 It is an IT curve diagram of the long-term cycle test of the BP / CNT@PVDF film of Example 1 under a high pressure of 1666 kPa;
[0039] Fig.12 The comparison diagrams of the mixed solution of BP and BP / CNT@PVDF in polar organic solvents in Example 1 before and after two weeks. DETAILED DESCRIPTION
[0040] The present invention provides a composite film based on a two-dimensional black phosphorus material, comprising two-dimensional layered black phosphorus, carbon nanotubes and polyvinylidene fluoride, wherein the two-dimensional layered black phosphorus and the carbon nanotubes are cross-linked with each other, and the polyvinylidene fluoride is coated on the surfaces of the two-dimensional layered black phosphorus and the carbon nanotubes.
[0041] In the present invention, the mass ratio of the two-dimensional layered black phosphorus and the carbon nanotubes is preferably (3-4):1, and more preferably (3.2-3.6):1; the mass ratio of the two-dimensional layered black phosphorus and polyvinylidene fluoride is preferably (3-4):1, and more preferably (3.2-3.6):1.
[0042] In the present invention, the thickness of the composite film is preferably 5 to 200 μm, more preferably 30 to 150 μm, and even more preferably 50 to 100 μm.
[0043] In the present invention, carbon nanotubes (CNT) are a commonly used nanomaterial for enhancing electrical conductivity. Combining carbon nanotubes with black phosphorus can increase the conductive path between two-dimensional black phosphorus and improve the conductive stability. Polyvinylidene fluoride is a typical flexible material. Combining polyvinylidene fluoride with black phosphorus can improve the stability of black phosphorus, solve the problem of easy oxidation, and provide conditions for flexible films.
[0044] The present invention adopts black phosphorus, carbon nanotubes and polyvinylidene fluoride composite, which greatly improves the conductivity, mechanical strength and stability of the film, filling the gap in the multifunctionality of existing materials.
[0045] The present invention provides a method for preparing a composite film based on a two-dimensional black phosphorus material as described in the above scheme, comprising the following steps:
[0046] mixing black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent to obtain a mixed solution;
[0047] The mixed solution is printed onto a substrate, and after curing and peeling, the composite film based on the two-dimensional black phosphorus material is obtained.
[0048] Unless otherwise specified, the materials and equipment used in the present invention are commercially available.
[0049] The invention mixes black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent to obtain a mixed solution.
[0050] In the present invention, the mixing preferably comprises the following steps:
[0051] Under the protection of inert gas, black phosphorus, carbon nanotubes and a first polar organic solvent are mixed and ball-milled to obtain a black phosphorus-carbon nanotube mixed solution;
[0052] The polyvinylidene fluoride and the second polar organic solvent are first mixed to obtain a polyvinylidene fluoride solution;
[0053] The black phosphorus-carbon nanotube mixed solution and the polyvinylidene fluoride solution are mixed for the second time.
[0054] In the present invention, the black phosphorus can be obtained by using commercial products known in the art or by self-production. In the present invention, the black phosphorus is self-production. In the present invention, the preparation method of the black phosphorus preferably comprises the following steps:
[0055] Under the protection of inert gas, red phosphorus is ball-milled to obtain black phosphorus.
[0056] In the present invention, the rotation speed of the ball mill is preferably 800 rpm, and the time is preferably 8 to 12 hours, and more preferably 9.5 to 11 hours.
[0057] The present invention preferably places the red phosphorus sample into a ball mill under the protection of an inert gas, and takes out the obtained black phosphorus sample to prevent the sample from being oxidized. In the present invention, the inert gas preferably includes nitrogen or argon, and requires that the water and oxygen contents are both less than 1 ppm.
[0058] After obtaining the black phosphorus, the present invention mixes and ball-mills the black phosphorus, carbon nanotubes and a first polar organic solvent under the protection of an inert gas to obtain a black phosphorus-carbon nanotube mixed solution.
[0059] In the present invention, the mass ratio of the black phosphorus to the carbon nanotubes is preferably (3-4):1, and more preferably (3.2-3.6):1; the mass ratio of the black phosphorus to the first polar organic solvent is preferably 3g:50mL. In the present invention, the first polar organic solvent preferably includes N-methylpyrrolidone.
[0060] In the present invention, the rotation speed of the mixing ball mill is preferably 300 to 400 rpm, and more preferably 320 to 380 rpm; the time of the mixing ball mill is preferably 12 to 24 hours, and more preferably 15 to 20 hours.
[0061] The invention forms chemical cross-linking between black phosphorus and carbon nanotubes through mixed ball milling to generate new COP and CP bonds.
[0062] The present invention prepares a black phosphorus-carbon nanotube mixed solution (BP-CNT mixed solution) by ball milling, which can ensure that the black phosphorus material and the carbon nanotubes are mixed uniformly and can reduce the possibility of black phosphorus oxidation during the mixing process.
[0063] The present invention preferably places the black phosphorus sample into the ball milling jar under the protection of an inert gas, and takes out the obtained black phosphorus-carbon nanotube mixed solution sample to prevent the sample from being oxidized. In the present invention, the inert gas preferably includes nitrogen or argon, and requires that: the water and oxygen contents are both less than 1 ppm; the inert gas can prevent the material from being oxidized and denatured during the mixed wet ball milling process.
[0064] After obtaining the black phosphorus-carbon nanotube mixed solution, the present invention first mixes polyvinylidene fluoride and a second polar organic solvent to obtain a polyvinylidene fluoride solution.
[0065] In the present invention, the mass ratio of the polyvinylidene fluoride to the volume ratio of the second polar organic solvent is preferably 1 g:10 mL. In the present invention, the first polar organic solvent preferably includes N-methylpyrrolidone.
[0066] The present invention adopts the first polar organic solvent and the second polar organic solvent, so that BP, CNT and PVDF can be mixed evenly to avoid precipitation.
[0067] In the present invention, the temperature of the first mixing is preferably 25 to 60° C., more preferably 30 to 50° C. In the present invention, the first mixing is preferably performed under stirring, and the stirring speed is preferably 400 to 500 rpm, more preferably 420 to 480 rpm.
[0068] The present invention completely dissolves the polyvinylidene fluoride through the first mixing to form a uniform polyvinylidene fluoride solution.
[0069] After obtaining the polyvinylidene fluoride solution, the present invention performs a second mixing of the black phosphorus-carbon nanotube mixed solution and the polyvinylidene fluoride solution.
[0070] In the present invention, the mass ratio of black phosphorus in the black phosphorus-carbon nanotube mixed solution to polyvinylidene fluoride in the polyvinylidene fluoride solution is preferably (3-4):1, and more preferably (3.2-3.6):1.
[0071] In the present invention, the second mixing is preferably performed under ultrasonic conditions; the power of the ultrasound is preferably 200 to 300 W, more preferably 220 to 280 W; the time of the ultrasound is preferably 1 to 3 h, more preferably 1.5 to 2.5 h.
[0072] After obtaining the mixed solution, the present invention prints the mixed solution onto a substrate, and after curing and peeling, obtains the composite film based on the two-dimensional black phosphorus material.
[0073] In the present invention, the substrate preferably includes a glass plate or a copper plate. The present invention has no special requirements for the printing equipment, and an appropriate suspension coating printing equipment can be selected according to actual conditions.
[0074] In the present invention, the printing speed is preferably 1 cm / s. In the present invention, the curing temperature is preferably 100 to 120° C., more preferably 105 to 115° C.; the curing time is preferably 12 to 24 hours, more preferably 15 to 20 hours.
[0075] In the present invention, the material on the substrate is automatically peeled off through solidification to become a self-supporting film material, namely the composite film.
[0076] In the present invention, before the curing, the printed material is preferably dried; the drying temperature is preferably 60° C., and the drying time is preferably 2 hours.
[0077] The present invention evenly disperses highly conductive carbon nanotubes in a black phosphorus matrix and uses the excellent mechanical flexibility and hydrophobicity of polyvinylidene fluoride to cover the entire composite film. This not only forms an effective physical barrier to block the intrusion of oxygen and moisture, but also establishes a stable conductive network, greatly improving the conductivity and chemical stability of the black phosphorus material.
[0078] The present invention provides the use of the composite film based on the two-dimensional black phosphorus material described in the above scheme or the composite film based on the two-dimensional black phosphorus material prepared by the preparation method described in the above scheme in a sensor.
[0079] In order to further illustrate the present invention, a composite film based on a two-dimensional black phosphorus material provided by the present invention, a preparation method thereof and an application thereof are described in detail below in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0080] Example 1
[0081] Under the protection of argon atmosphere in the glove box, the water and oxygen contents are both less than 1ppm. Select a 100mL stainless steel vacuum ball mill and stainless steel grinding balls, weigh 10 grams of red phosphorus (RP), and put it into the ball mill in the glove box. The filling degree is 1 / 2 of the volume of the ball mill. After the ball mill is sealed, install it on the ball mill, set the ball mill parameters, the speed is 400rpm, the time is 48h, start the ball mill for ball milling, and obtain high-purity black phosphorus (BP) powder. After the ball milling is completed, stop the ball mill, carefully take out the ball mill to prevent the sample from oxidizing, open the ball mill in the glove box, and take out the high-purity black phosphorus (BP) powder.
[0082] Under the protection of argon atmosphere in the glove box, the water and oxygen contents are both less than 1ppm. Weigh 3g of black phosphorus (BP) and 1g of carbon nanotubes (CNT) into the ball mill, and add 50mL of N-methylpyrrolidone (NMP) to fully wet the black phosphorus and carbon nanotubes. Seal the ball mill and install it on the ball mill. Set the ball mill parameters: the speed is 300rpm, the time is 24h, and start the ball mill for mixing. After the mixing is completed, stop the ball mill, carefully take out the ball mill, open the ball mill in the glove box, and take out the BP-CNT mixture.
[0083] Weigh 1 g of polyvinylidene fluoride particles, add the polyvinylidene fluoride particles into 10 mL of NMP, and stir using a magnetic stirrer at a stirring speed of 400 rpm and a temperature of 25° C. until the polyvinylidene fluoride is completely dissolved to form a uniform polyvinylidene fluoride solution.
[0084] The BP-CNT solution was gradually added to the polyvinylidene fluoride solution, and the mixed solution was ultrasonically treated using an ultrasonic device for 1 h at a power of 200 W to ensure that the solution was uniform and free of precipitation, thereby obtaining a BP / CNT@PVDF solution.
[0085] Using appropriate suspension printing equipment, the BP / CNT@PVDF solution was printed on a smooth copper foil substrate, and the printing parameters were controlled: a printing speed of 1 cm / s and a layer thickness of 50 μm to prepare a film of the desired thickness. After printing, it was dried at 60°C for 2 hours and cured at 120°C for 12 hours to obtain the final composite film, which was recorded as BP / CNT@PVDF film.
[0086] Structure and performance testing
[0087] Figure 1 This is a scanning electron microscope image of the BP / CNT@PVDF film of Example 1, with a scale of 100 μm. Figure 1 As shown, the BP / CNT@PVDF film formed a rich and uniform conductive structure, showing good dispersion and consistency.
[0088] Figure 2 Another SEM image of the BP / CNT@PVDF film of Example 1, with a scale of 5 μm. Figure 2 In the film, black phosphorus maintains a good layered structure under the composite effect of polyvinylidene fluoride, and carbon nanotubes form a stable conductive path in it, which significantly improves the conductive properties of the film.
[0089] Figure 3 The SEM thickness image of the BP / CNT@PVDF film of Example 1 is shown in FIG. 1 , and the scale is 250 μm. Figure 3 As shown, the thickness of the BP / CNT@PVDF film is 50 μm, indicating that the BP / CNT@PVDF film has excellent portability and wearing comfort, which meets the requirements for its application in flexible electronic devices.
[0090] Figure 4 Figure 1 is a physical picture of the BP / CNT@PVDF film of Example 1, where (a) is an unfolded view and (b) is a rolled view. Figure 4 As shown, the BP / CNT@PVDF film exhibits good flexibility and ductility and can adapt to various deformation requirements.
[0091] Figure 5 : This is a comparison of the X-ray photoelectron spectra of the BP / CNT@PVDF film of Example 1 and pure black phosphorus. Figure 5As shown, new chemical bonds are formed between the composited black phosphorus, carbon nanotubes and polyvinylidene fluoride, indicating that a chemical reaction occurs during the mixing process, which enhances the stability and synergistic effect of the overall material.
[0092] Figure 6 is the X-ray diffraction pattern of the BP / CNT@PVDF film of Example 1, as shown Figure 6 As shown in the figure, new diffraction peaks appeared after sufficient mixing, which shows that black phosphorus, carbon nanotubes and polyvinylidene fluoride are mixed to form BP / CNT@PVDF material.
[0093] Figure 7 The Raman spectra of the BP / CNT@PVDF film and PVDF, BP and CNT of Example 1 are shown in FIG. Figure 7 As shown, there are characteristic peaks corresponding to each component after compounding, indicating that there is a good interaction between the various components in the BP / CNT@PVDF film material.
[0094] Figure 8 is the IV curve of the BP / CNT@PVDF film of Example 1 under different pressures, Figure 8 The test results show that within the pressure range of 0 to 3333 kPa, the resistance of the film changes linearly with pressure, indicating that its structure is stable and can maintain stable electrical properties within a wide pressure range.
[0095] Fig. 9 is the IT curve of the BP / CNT@PVDF film of Example 1 under different pressures, Fig. 9 The test results show that when the pressure increases from 25kPa to 3333kPa, the current response of the film also increases accordingly, demonstrating excellent repeatability and sensitivity.
[0096] Fig.10 is the IP curve of the BP / CNT@PVDF film of Example 1 under gradually increasing pressure, Fig.10 The test results further prove that the current response of the film changes significantly during the pressure increase process, indicating its potential in stress sensing and sensing applications.
[0097] Fig.11 It is the IT curve of the BP / CNT@PVDF film of Example 1 under a long-term cycle test at a high pressure of 1666 kPa. Fig.11 The test results prove that the film can still maintain a stable pressure response under high pressure and long-term testing, demonstrating the stable pressure sensing application capability of the composite material. This further illustrates that the BP / CNT@PVDF film prepared by the present invention is not easily oxidized, can work stably, and has strong conductive stability.
[0098] Fig.12 The comparison diagrams of the mixed solutions of BP and BP / CNT@PVDF in polar organic solvents (NMP) of Example 1 before and after two weeks. Among them, (a) is the mixed solution of BP in polar organic solvents, and the specific preparation process is: 100 mg of black phosphorus (BP) powder is dissolved in 10 mL; (b) is the image after it is placed at room temperature for two weeks. (c) is the mixed solution of BP / CNT@PVDF in polar organic solvents (i.e., the BP / CNT@PVDF solution obtained in Example 1); (d) is the image after it is placed for two weeks. By comparing the images before and after being placed at room temperature for two weeks, it can be seen that the pure BP mixed solution will undergo oxidative discoloration and sedimentation (the color becomes lighter, indicating oxidation) after being placed for a period of time, and the BP / CNT@PVDF mixed solution will not undergo oxidative discoloration, showing that the antioxidant capacity and stability of the composite material (i.e., the BP / CNT@PVDF film obtained by the present invention) are enhanced.
[0099] In summary, the above test results jointly verify the superior performance and broad application prospects of BP / CNT@PVDF film.
[0100] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A composite film based on two-dimensional black phosphorus material, comprising two-dimensional layered black phosphorus, carbon nanotubes and polyvinylidene fluoride, wherein the two-dimensional layered black phosphorus and the carbon nanotubes are cross-linked with each other, and the polyvinylidene fluoride is coated on the surface of the two-dimensional layered black phosphorus and the carbon nanotubes.
2. The composite film according to claim 1, characterized in that The mass ratio of the two-dimensional layered black phosphorus to the carbon nanotubes is (3-4):
1.
3. The composite film according to claim 1, characterized in that The mass ratio of the two-dimensional layered black phosphorus to polyvinylidene fluoride is (3-4):
1.
4. The composite film according to any one of claims 1 to 3, characterized in that: The thickness of the composite film is 5 to 200 μm.
5. The method for preparing a composite film based on a two-dimensional black phosphorus material according to any one of claims 1 to 4, comprising the following steps: mixing black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent to obtain a mixed solution; The mixed solution is printed onto a substrate, cured, and peeled off to obtain the composite film based on the two-dimensional black phosphorus material.
6. The preparation method according to claim 5, characterized in that: The mixing of black phosphorus, carbon nanotubes, polyvinylidene fluoride and a polar organic solvent comprises the following steps: Under the protection of inert gas, black phosphorus, carbon nanotubes and a first polar organic solvent are mixed and ball-milled to obtain a black phosphorus-carbon nanotube mixed solution; The polyvinylidene fluoride and the second polar organic solvent are first mixed to obtain a polyvinylidene fluoride solution; The black phosphorus-carbon nanotube mixed solution and the polyvinylidene fluoride solution are mixed for the second time.
7. The preparation method according to claim 6, characterized in that: The rotating speed of the mixing ball mill is 300-400 rpm, and the time is 12-24 hours.
8. The preparation method according to claim 6, characterized in that: The second mixing is performed under ultrasonic conditions; the power of the ultrasonic is 200-300W, and the time is 1-3h.
9. The preparation method according to claim 6, characterized in that: The curing temperature is 100-120° C. and the curing time is 12-24 hours.
10. Use of the composite film based on two-dimensional black phosphorus material according to any one of claims 1 to 4 or the composite film based on two-dimensional black phosphorus material prepared by the preparation method according to any one of claims 5 to 9 in a sensor.
Citation Information
Patent Citations
Self-lubricating wear-resistant composite film containing nano two-dimensional black-phosphorus and preparation method of composite film
CN108395553A
Black phosphorus-based negative electrode material and preparation method thereof
CN113437281A
Black phosphorus-carbon composite material as well as preparation method and application thereof
CN115172711A
Black phosphorus non-woven fabric and preparation method thereof
CN117535870A
Circuit for protecting Electronic Controller Unit, Electronic Controller Unit thereof, and system for assisting steering
KR102640428B1
